Autoimmune/Inflammatory Syndrome Induced by Adjuvants - A. A. Zayaeva; S. I. R. Younsi; A. I. Zausalina; G. N. Коshukova; A. V. Кlimchuk; G. A. Younsi (Архивъ внутренней медицины)
ASIA syndrome (autoimmune/inflammatory syndrome induced by adjuvants) is a group of autoimmune diseases caused by adjuvants that have the ability to induce immune responses. The syndrome includes five immune-mediated conditions that are associated with prior exposure to various trigger factors, such as siliconosis, macrophage myofasciitis syndrome, Persian Gulf syndrome, sick building syndrome, and post-vaccination autoimmune events. The development of ASIA syndrome is associated with an individual genetic predisposition and occurs as a result of the combined effect of exogenous and endogenous factors that trigger an autoimmune response. In this case, the reaction of the immune system can be unpredictable. The article presents the diagnostic criteria for the syndrome, as well as its clinical, laboratory and morphological manifestations. The spectrum of clinical manifestations of the autoimmune/inflammatory syndrome induced by adjuvants is extensive and affects almost all systems of the human body. At the same time, its characteristic feature is the regression of clinical, laboratory and morphological manifestations after removal of the adjuvant. There is no doubt that ASIA syndrome has clarified the role of adjuvants in the development of autoimmune processes. This should be taken into account when creating safe vaccines, silicone implants, fillers and other medical devices with minimal side effects. In addition, medical professionals should raise patients’ awareness of the side effects of using certain cosmetic procedures and the use of silicone implants, for which it is necessary to include a description of the etiology, pathogenesis, diagnosis and treatment of ASIA syndrome in teaching aids for students, residents and doctors of various specialties as a separate nosological unit.